2018
DOI: 10.1111/iwj.12951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain in chronic wounds: A survey of Australian health care practitioners

Abstract: Pain associated with chronic wounds can delay wound healing, affects quality of life, and has a major impact on physical, emotional, and cognitive function. However, wound-related pain is often under-assessed and may therefore be suboptimally managed. The aim of this study was to describe the assessment practices used to assess chronic wound pain by health practitioners in Australia. A structured self-administered questionnaire was posted to members of an Australian national wound care organisation, whose memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
2
26
1
Order By: Relevance
“…There may be numerous reasons for the high percentage of severe pain in the present study, but inadequate pain management is probably a major contribution. Research indicates healthcare professionals do not comply with well‐established guidelines for best practice of wound care when it comes to pain assessment (Franck & Bruce, 2009; Frescos, 2018), and are insecure about the optimum pharmacological management of non‐malignant pain in older persons (Barber & Gibson, 2009). In addition, stoicism and fear of addiction among patient with chronic venous ulcers, may lead to a tendency to take analgesics less frequently or at a lower dose than prescribed (Sale et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There may be numerous reasons for the high percentage of severe pain in the present study, but inadequate pain management is probably a major contribution. Research indicates healthcare professionals do not comply with well‐established guidelines for best practice of wound care when it comes to pain assessment (Franck & Bruce, 2009; Frescos, 2018), and are insecure about the optimum pharmacological management of non‐malignant pain in older persons (Barber & Gibson, 2009). In addition, stoicism and fear of addiction among patient with chronic venous ulcers, may lead to a tendency to take analgesics less frequently or at a lower dose than prescribed (Sale et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pain assessment and management are identified as a main category of the ‘wound management and assessment’ area for registered nurses providing care for chronic wounds (Kielo et al, 2019). However, wound care researchers report that persistent ulcer‐related pain is either dismissed by healthcare providers or inappropriately assessed (Frescos, 2018; Green et al, 2018). Presumably, lack of knowledge (Green et al, 2018) or time (Frescos, 2018; Green et al, 2018) may be reasons for inadequate pain assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review demonstrated nurse‐led wound care to reduce pain on multiple occasions, even with different methods of nurse‐led intervention. Frescos (2018) reinforced this finding, with nurses more likely to conduct a pain assessment during wound care, in comparison with other healthcare practitioners. Pain is under‐assessed and often dismissed by healthcare practitioners; therefore, pain assessment should be a priority in wound care.…”
Section: Discussionmentioning
confidence: 92%
“…Chronic wounds are susceptible to pain because of complex physiological processes involving chronic inflammation, neuropathy and infection, and up to 80% of people experience pain with chronic wounds (Woo & Sibbald, 2008). Therefore, people with chronic wounds are often more concerned about pain management rather than wound healing (Frescos, 2018). The literature review demonstrated nurse‐led wound care to reduce pain on multiple occasions, even with different methods of nurse‐led intervention.…”
Section: Discussionmentioning
confidence: 99%